Visceral fat-to-muscle ratio guides spontaneous closure in post-sepsis duodenal fistula: a body composition divergence beyond visceral-subcutaneous fat ratio - Tang, Qian; Li, Wuhan; Xu, Xin; Zhao, Risheng; Zhao, Yunzhao; Yao, Zheng (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to investigate whether body composition parameters (visceral fat area/total abdominal muscle area index, VFA/TAMAI; visceral-to-subcutaneous fat ratio, VFA/SFA) predict spontaneous closure in duodenal fistula patients after sepsis resolution.MethodsA multicenter retrospective study enrolled 104 duodenal fistula patients with controlled sepsis treated between 2019 and 2025. Standardized management included infection control and nutritional support. Restricted cubic spline regression identified optimal cutoffs for VFA/TAMAI and VFA/SFA. Cox proportional hazards models evaluated associations with 90-day spontaneous closure, with inverse probability treatment weighting (IPTW) and propensity score matching (PSM) addressing confounding.Results52.9% (55/104) achieved spontaneous closure within 90 days (median time: 31 days). Elevated VFA/TAMAI (≥3.20, 31.7% patients) independently predicted reduced closure likelihood (adjusted HR = 0.59, 95%CI:0.42–0.85, P = 0.004), while VFA/SFA showed no prognostic value (P > 0.05). Incorporation of VFA/TAMAI significantly improved predictive accuracy (C-index increased from 0.67 to 0.72, P = 0.013). Sensitivity analyses confirmed VFA/TAMAI≥3.20 remained predictive after IPTW adjustment (HR = 0.38, 95%CI:0.17–0.84) and PSM (HR = 0.39, 95%CI:0.19–0.83).ConclusionVFA/TAMAI serves as a robust predictor of spontaneous closure in post-sepsis duodenal fistula, with the threshold of 3.20 identifying high-risk patients requiring intensified nutritional-metabolic interventions. These findings highlight body composition monitoring as a critical adjunct to conventional nutritional management.